THE RECONSTRUCTION OF EGYPTIAN WOMEN'S ROLES IN THE NETFLIX SERIES AL-BACHTSU ‘AN OLA - Shinta Fitria Utami; Ferry Saputra (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2022)
The patriarchy that prevails in Egypt is frequently blamed for the domestication of women in that country. Al-Bachtsu 'an Ola, a Netflix series, challenges this narrative by showing a different notion about current Egyptian women. This paper examines the role of Egyptian women in today's modern society. This study examines the role of Egyptian women in today's modern society. The analysis examined situations and dialogues that reveal the reconstruction of women's roles in modern Egyptian society using feminist literary criticism as a perspective. The findings showed that the series depicts modern Egyptian women redefining their social roles in public.